Nature-based strategies for heat mitigation: shade index modeling of cover crops in rooftop agriculture - Castro Bedriñana, Jorge (2026)
Under extreme environmental conditions, interplant facilitation influences the growth and yield of heat-sensitive crops. In this study, the shade index of three cover plants for growing tomato crops on green roofs in Peru's high jungle was evaluated to generate a mathematical model to could be used as a standard in other studies. The mathematical models estimated the shade indices of Mucuna pruriens, Luffa cylindrica, and Cyclanthera pedata as tomato cover plants. The quantitative analysis carried out with the weekly growth data of the cover plants allowed us to determine the shade index, showing that Mucuna pruriens is the best heat-mitigating indicator plant due to its best ecophysiological condition. This model could be adjusted to any plant and facilitate the growth of solar radiation and high temperature-sensitive crops. In this study, Mucuna pruriens is shown as a heat-mitigating plant due to its better ecophysiological condition than Luffa cylindrica and Cyclanthera pedata. Mucuna pruriens reached 100% shade, while Luffa cylindrica and Cyclanthera pedata had 33.40% and 17.00% shade. This mathematical model could serve as a general standard for other studies identifying the shade index of cover plants for different crops susceptible to high heat and light environmental conditions in high jungles.